2017
DOI: 10.1111/idj.12259
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body mass index and dental caries in children, and the influence of socio-economic status

Abstract: BMI was not associated with dental caries prevalence and experience in this population. The association of BMI with dental caries varied across SES categories. In the high-SES category, overweight children experienced fewer caries than did normal-weight children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 38 publications
2
30
0
4
Order By: Relevance
“…Moreover, most of these studies conducted only basic statistical analyses or did not account for potentially confounding factors . Other studies reported no significant associations between dental caries and BMI after accounting for socioeconomic factors . Similarly, two studies from India and Brazil observed no significant associations between caries and childhood obesity.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, most of these studies conducted only basic statistical analyses or did not account for potentially confounding factors . Other studies reported no significant associations between dental caries and BMI after accounting for socioeconomic factors . Similarly, two studies from India and Brazil observed no significant associations between caries and childhood obesity.…”
Section: Discussionmentioning
confidence: 92%
“…Given that ultra-processed food is rich in sugars and saturated fat [Zobel et al, 2016], we assume that such kinds of food might also increase dental caries prevalence and severity, but this still needs to be proved. Children in low-and middle-income countries usually follow poor preventive oral hygiene practices, which increases the risk of dental caries [Kumar et al, 2017]. The significant differences between countries with different income might be a reflection of socioeconomic status and parents' education and occupation.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, in recent years researchers have gradually realized that there might be some differences between underweight and normal weight in regard to dental caries. Some researchers found that underweight children had statistically significantly more dental caries than children with normal weight [Yang et al, 2015;Kumar et al, 2017]. They suggested that children who were picky eaters were more likely to be served kinds of unhealthy food to stimulate their appetite, which consequently induced underweight and dental caries [Dubois et al, 2007;Norberg et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Kumar in India did not find an association between BMI and caries in children. However, the analysis of the group belonging to an affluent socio-economic level showed that overweight children had less dental caries than normal weight children (13) . However, other studies found an association between overweight and dental caries prevalence (14,15) .…”
Section: Bmimentioning
confidence: 90%